Non-equivalence of the microcanonical and canonical ensembles in a bosonic Josephson junction - González-García, L.A.; Zamora-Zamora, R.A.; Paredes, R. (Revista Mexicana de Física, 2011)
We investigate the thermodynamic properties of a bosonic Josephson junction in the full quantum approach and, in particular, we concentrate in studying the thermal averages of one- and two-body properties below and above the transition from delocalized to self-trapped regimes. This temperature dependence is determined by using the fact that at equilibrium the microcanonical and canonical ensembles should be equivalent. To establish the robustness of the equilibrium state, we first study a one body property and show numerically that any arbitrary state localized in energy, when evolved, reaches a stationary or equilibrium state. Comparison among averages of one- and two-body properties in the microcanonical and canonical ensembles reveals discrepances, thus leading to non-equivalence among these ensembles. Such averages differences can be attributed to the fact that the Hilbert space of the system scales as its size N, and consequently, the entropy does not scale as N. We further find as a natural consequence of studying the finite bosonic Josephson junction in the two-mode Bose Hubbard context, that positive and negative temperatures are obtained. This result can be generalized for any finite optical lattice.